Relationship Anxiety with Stigma to Tuberculosis Patients in Student at One Private University in Western Indonesia - Nadia Gloria Demanora; Rara Teresia; Yesi Carolina; Ballsy C.A Pangkey; Sumiaty Aiba (Sekolah Tinggi Ilmu Kesehatan Kendal, 2022)
Tuberculosis sufferers are infected persons with the infectious disease caused by mycobacterium tuberculosis. Tuberculosis transmission through air and droplets, like coughing or sneezing from patients, caused stigma in the social community with discrimination is fear, worry, anxiety adjacent, and no interaction with tuberculosis patients diagnosed. Stigma in tuberculosis patients can drop the bounce of an individual right in a social aspect. Aim study was to evidence the relationship between anxiety and stigma among tuberculosis patients in students at one private university in western Indonesia. This study was descriptive correlational research, consisting of a student of the active year 2018 as respondents, using a cross-sectional approach. Analysis data was univariate, and bivariate to assess the relationship between anxiety with stigma by the Somers d test. The result study was univariate, showed the relationship between anxiety and stigma level to tuberculosis in the lower category, were 94 respondents by percentage 52% of the 179 respondents, and a bivariate showed a significant relationship between anxiety with stigma to tuberculosis patients, p=0.025 of the confidence p<0.05. Relationship anxiety with stigma to tuberculosis patients in respondents is significantly low, because they have precepts and the better knowledge from learning education at one private university in western Indonesia.